2014
DOI: 10.3109/10715762.2014.906592
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal mitochondrial fusion–fission balance contributes to the progression of experimental sepsis

Abstract: Sepsis-associated multiple organ failure is a major cause of mortality characterized by a massive increase of reactive oxygen and nitrogen species (ROS/RNS) and mitochondrial dysfunction. Despite intensive research, determining events in the progression or reversal of the disease are incompletely understood. Herein, we studied two prototype sepsis models: endotoxemia and cecal ligation and puncture (CLP)-which showed very different lethality rates (2.5% and 67%, respectively)-, evaluated iNOS, ROS and respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 50 publications
7
59
0
Order By: Relevance
“…In a preclinical animal model of sepsis (CLP) there was an abnormal balance of fission and fusion responses thought to contribute to cellular injury and apoptosis. The in vivo pretreatment with mdivi-1 (Drp1 inhibitor) significantly attenuated mitochondrial dysfunction and apoptosis in CLP (52). …”
Section: Resultsmentioning
confidence: 99%
“…In a preclinical animal model of sepsis (CLP) there was an abnormal balance of fission and fusion responses thought to contribute to cellular injury and apoptosis. The in vivo pretreatment with mdivi-1 (Drp1 inhibitor) significantly attenuated mitochondrial dysfunction and apoptosis in CLP (52). …”
Section: Resultsmentioning
confidence: 99%
“…) and liver (Gonzalez et al. ), where in vivo administration of Mdivi‐1 conferred cytoprotection of important cell types in these organs (i.e., retinal ganglion cells, renal tubular epithelial cells, and hepatocytes, respectively). Despite these promising results, many challenges (as discussed in the next section) await before Mdivi‐1 might be suitable for patients.…”
Section: Therapeutic Potential Of Mdivi‐1mentioning
confidence: 99%
“…Perturbation of the mitochondrial fission-fusion balance can aggravate ROS-induced tissue injury [50]. Accordingly, we found that increased accumulation of Opa1-S by AZT caused mitochondrial fragmentation (Fig.…”
Section: Discussionmentioning
confidence: 69%